Ablation behaviour of Csf/ZrB2-SiC composites fabricated by direct ink writing and reactive melt infiltration. Issue 8 (July 2023) - Lu, Jun; Ni, Dewei; Chen, Bowen; Cai, Feiyan; Xuegang, Zou; Zhang, Xiangyu; Ding, Yusheng; Dong, Shaoming
Abstract: Pitch-based short carbon fibres reinforced Csf /ZrB2 -SiC composites were fabricated by direct ink writing of short carbon fibres, followed by slurry impregnation and reactive melt infiltration. Ablation behaviour of the Csf /ZrB2 -SiC composite was studied by air plasma test. It is indicated that the skeleton of the oriented short carbon fibres provides heat diffusion channels. Consequently, temperatures at the ablation surface are as low as ∼1730 o C and ∼2000 o C respectively at 4 MW/m 2 and 5 MW/m 2 . The composite presents outstanding ablation-resistant performance with a linear recession rate of ∼ − 0.04 µm/s and mass recession rate of ∼ − 3.40 mg/s at 4 MW/m 2, ∼ − 0.17 µm/s and ∼ 3.58 mg/s at 5 MW/m 2 . It is revealed that the fibres area and matrix area of the composite present different ablation mechanisms. The fibres area is ablated severely, while the matrix area presents excellent ablation-resistance with continuous ZrO2 -SiO2 protective layer.